Association between endometrial thickness and neonatal outcomes in intrauterine insemination cycles: a retrospective analysis of 1,016 live-born singletons - Jialyu Huang; Jiaying Lin; Xuefeng Lu; Hongyuan Gao; Ning Song; Renfei Cai; Yanping Kuang (BMC, 2020)
Abstract Background Decreased endometrial thickness (EMT) has been suggested to be associated with reduced birthweight of in vitro fertilization/intracytoplasmic sperm injection (IVF/ICSI) newborns. Considering the differences in ovarian stimulation degree and laboratory procedures between IVF/ICSI and IUI treatment, we aim to investigate whether EMT has any influence on IUI infant outcomes as well. Methods This was a retrospective cohort study of 1016 patients who had singleton livebirths after IUI treatment cycles from January 2008 to December 2018 at a tertiary-care academic medical center in China. Patients were categorized into three groups by the 10th and 90th percentile of peak EMT: ≤7.6, 7.7-13.0 and ≥ 13.1 mm. The primary outcomes of the study were preterm birth (PTB), low birthweight (LBW) and small-for-gestational age (SGA). Multiple regression analyses were performed after controlling for a variety of potential confounders. Results No significant differences were found among the three groups in gestational age, birthweight and birthweight Z-score. Compared with the EMT 7.7-13.0 mm group, the incidences of PTB, LBW and SGA were 5.5% (adjusted odds ratio [aOR] 0.81, 95% confidence interval [CI] 0.33-2.01), 6.4% (aOR 1.44, 95% CI 0.58-3.58) and 7.3% (aOR 1.21, 95% CI 0.53-2.76) in the EMT ≤7.6 mm group, respectively. Similarly, EMT ≥13.1 mm was not significantly associated with risks of PTB (aOR 0.63, 95% CI 0.24-1.65), LBW (aOR 0.57, 95% CI 0.17-1.95) and SGA (aOR 0.73, 95% CI 0.28-1.92). The odds of other adverse neonatal outcomes, including macrosomia, large-for-gestational age and major congenital malformations, did not show significant differences before and after adjustment in both EMT ≤7.6 and ≥ 13.1 mm groups. Conclusions EMT is not independently associated with adverse perinatal outcomes in IUI cycles. This novel finding would provide reassuring information for IUI patients with thin endometrial linings regarding their neonatal health. However, further prospective cohort studies with larger datasets are needed to confirm the conclusion.